DNA metabarcoding focusing on the plankton community: an effective approach to reconstruct the paleo-environment - Yasuhide Nakamura; Eri Ogiso-Tanaka; Koji Seto; Takuto Ando; Kota Katsuki; Yoshiki Saito (Scientific Reports, 2023)
Abstract DNA metabarcoding (DNA-MB) targeting the whole plankton community is a promising approach in studies of sediment samples from water bodies, but its effectiveness in ancient material is not well demonstrated. We applied DNA-MB of plankton in a sediment core to reconstruct the paleo-environment of Lake Shinji, Japan, through a marine lagoon/freshwater lake transition during the past 2300 years. We interpreted core-sample plankton taxonomy and habitat by reference to the modern plankton community in water samples. OTUs (operational taxonomic units) belonging to Dictyochophyceae were 81.05% of the total reads in sediments. However, Ciliophora, Copepoda and Labyrinthulea formed the majority of plankton taxa in the water samples, suggesting that they are under-represented in sediment. A drastic change in plankton composition correlated with a large decrease in sediment sulfur concentration, implying the change of aquatic environment from marine lagoon to freshwater lake. This event took place ca. 1200 CE in Lake Shinji. A 250 year-long transitional period followed, during which the total DNA sequence reads were very low. This suggests that salinity fluctuations created a hostile environment for both marine and freshwater plankton species. Our results show that DNA-MB of the whole plankton community is effective in reconstructing paleo-environments.